2020
DOI: 10.1007/s10834-020-09668-x
|View full text |Cite
|
Sign up to set email alerts
|

Career or Flexible Work Arrangements? Gender Differences in Self-employment in a Young Market Economy

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Studies have shown that entrepreneurship is not an overnight process. Instead, there is a buffer period ( Buttler and Sierminska, 2020 ) before achieving full entrepreneurship. During this time, necessary and practical entrepreneurship-related experience is acquired.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Studies have shown that entrepreneurship is not an overnight process. Instead, there is a buffer period ( Buttler and Sierminska, 2020 ) before achieving full entrepreneurship. During this time, necessary and practical entrepreneurship-related experience is acquired.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Due to the high prevalence of grandparents in households of European countries as studied by Dominik Buttler and Eva Sierminsk (2020), women (especially those with small children) tend to become self-employed based on income trading under more flexible work arrangements this relates to the importance work-life balance. However, financial restrictions have strongly influenced the entry of individuals into starting their own firms (Buttler & Sierminska, 2020) whereas, in Pakistan majority of the youth invests in acquiring higher level education to find a suitable job, as its people have very limited resources and do not have very good opportunities to build a start-up with the costs being too high.…”
Section: Discussion With Limitations and Future Research Recommendationsmentioning
confidence: 99%
“…Consequently, these women will tend to suffer from lower levels of self-confidence, a lack of experience and insufficient qualifications compared to male entrepreneurs coming out of employment in a leadership position, with the goal of self-realization and the desire for professional independence very much in their minds (Franke, 2012 ; Meliou and Mallett, 2022 ). At the same time, the study by Buttler and Sierminska ( 2019 ) points out that flexibility, a job matching their competences and opportunities for growth are more important motives for female entrepreneurs, while their male counterparts are seeking independence, more income and less stress in self-employed work.…”
Section: Gender Aspects In Mature Entrepreneurship In the Literaturementioning
confidence: 99%
“…Higher income , access to capital or, conversely, debt seem to have a significant effect on transitions into self-employment for both mature men and women (Zissimopoulos and Karoly, 2007 ; Global Entrepreneurship Monitor (GEM), 2017 ; Buttler and Sierminska, 2019 ; KfW Bankengruppe, 2022 ). Due to interruptions in their working careers (involving high levels of unpaid and/or part-time work), a high number of women are less able to accumulate savings to use later for their own businesses (Franke, 2012 ; Buttler and Sierminska, 2019 ).…”
Section: Gender Aspects In Mature Entrepreneurship In the Literaturementioning
confidence: 99%